Quantification and rationalization of the higher affinity of sodium over potassium to protein surfaces - Vrbka, Lubos; Vondrásek, Jirí; Jagoda-Cwiklik, Barbara; Vácha, Robert; Jungwirth, Pavel (Proceedings of the National Academy of Sciences of the United States of America, 2006)
For a series of different proteins, including a structural protein, enzyme, inhibitor, protein marker, and a charge-transfer system, we have quantified the higher affinity of Na+ over K+ to the protein surface by means of molecular dynamics simulations and conductivity measurements. Both approaches show that sodium binds at least twice as strongly to the protein surface than potassium does with this effect being present in all proteins under study. Different parts of the protein exterior are responsible to a varying degree for the higher surface affinity of sodium, with the charged carboxylic groups of aspartate and glutamate playing the most important role. Therefore, local ion pairing is the key to the surface preference of sodium over potassium, which is further demonstrated and quantified by simulations of glutamate and aspartate in the form of isolated amino acids as well as short oligopeptides. As a matter of fact, the effect is already present at the level of preferential pairing of the smallest carboxylate anions, formate or acetate, with Na+ versus K+, as shown by molecular dynamics and ab initio quantum chemical calculations. By quantifying and rationalizing the higher preference of sodium over potassium to protein surfaces, the present study opens a way to molecular understanding of many ion-specific (Hofmeister) phenomena involving protein interactions in salt solutions.
Keywords: Molecular Sequence Data; Potassium; Protein Binding; Computer Simulation; draslík; proteiny; počítačová simulace; povrchové vlastnosti; Ions; teoretické modely; skot; Models, Theoretical; ionty; Surface Properties; zvířata; vazba proteinů; Cattle; sodík; molekulární sekvence - údaje; Sodium; Proteins; Animals